Hypoxemia without Respiratory Distress: Hereditary Hemorrhagic Telangiectasia in a Child - McCann, Michael D.; Newlon, Claire; Krawiec, Conrad (Journal of Pediatric Intensive Care, 2020)
Hereditary hemorrhagic telangiectasia (HHT) is an underrecognized genetic disorder of vascular development in pediatric patients. Its presentation can range from mild cutaneous findings to life-threatening hemorrhage from arteriovenous malformations. Clinical diagnosis can be challenging in the pediatric population as disease manifestations evolve over time and may be difficult to identify in younger patients. This case highlights how nonspecific symptoms and signs in the preanesthesia period can be misleading, potentially placing a patient with unrecognized HHT at risk for significant morbidity and mortality.
Keywords: hereditary hemorrhagic telangiectasia; pediatric; hypoxemia